1990
DOI: 10.1159/000276162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dosing Schedule on Aminoglycoside Ototoxicity: Comparative Cochlear Ototoxicity of Amikacin and Isepamicin

Abstract: The effect of the dosing schedule on aminoglycoside ototoxicity was investigated in the guinea pig. The animals were given amikacin or isepamicin either by once-daily intramuscular injection of 200 mg/kg or by twice-daily injections of 100 mg/kg for 28 days. The once-daily treatment induced a lesser degree of ototoxicity than the twice-daily injections, which may indicate that the once-daily treatment therapy has a potential value in the clinical use of aminoglycoside antibiotics. Isepamicin sulfate is a new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In terms of renal toxicity, isepamicin compared favorably with amikacin given at low doses in rats (30). Moreover, Takumida et al (34) showed in guinea pigs that the once-daily treatment with amikacin and isepamicin induced a lesser degree of ototoxicity than the twice-daily injection but that the degree of ototoxicity induced by isepamicin was markedly less than that of amikacin.…”
mentioning
confidence: 99%
“…In terms of renal toxicity, isepamicin compared favorably with amikacin given at low doses in rats (30). Moreover, Takumida et al (34) showed in guinea pigs that the once-daily treatment with amikacin and isepamicin induced a lesser degree of ototoxicity than the twice-daily injection but that the degree of ototoxicity induced by isepamicin was markedly less than that of amikacin.…”
mentioning
confidence: 99%
“…Attempts to elucidate the mechanism of toxicity or to prevent the adverse effects have previously been unsuccessful. Recent studies have revealed that the once-daily treatment regimen of aminoglycosides induces the lowest degree of ototoxicity and have confirmed the efficacy and safety of a once-daily regimen for clinical use [3,4], Prevention of ototoxicity using several kinds of drugs, however, has been unsuccessful [7,8],…”
Section: Discussionmentioning
confidence: 99%
“…The degree of damage de pends not only on the particular antibiotic used but also on the dose schedule and the total dose [3,4], Concerning this group of drugs, comparative studies of ototoxicity KARGER ©1996 S. Karger AG. Basel 0301-1569/96/0582-0068S 10.00/0 E-Mail kargcr@kargcr.ch F ax+ 41 61 306 12 34 patterns have revealed that the most pronounced changes are found after neomycin treatment, whereas the least changes are evident after netilmicin treatment [1,2], Recent studies have also revealed that the dosing schedule also influences the development of ototoxicity [3,4], A once-daily dose therapy has recently been suggested for clinical use instead of an administration of aminoglyco side 2 or 3 times per day. This may be partly explained by better patient compliance, which is also convenient for the physician [5], A number of studies have confirmed the efficacy and safety of a once-daily regimen for clinical use [5,6], The risk of ototoxic development has been signifi cantly lower in a once-daily treatment than one given 2 or 3 times per day [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the low therapeutic/toxic ratio of ex isting aminoglycosides like streptomycin, gen tamicin, netilmicin, tobramycin and amikacin has led to a search for safer drugs. Isepamicin is a semi-synthetic drug derived from genta micin B which is expected to have a clinical ef ficacy similar to that of amikacin but with less toxicity [1][2][3]. In this paper we describe the in vitro activity of isepamicin and compare it to amikacin against relatively resistant clinical isolates from a tertiary-care center.…”
Section: Introductionmentioning
confidence: 99%